Sosialisasi Pengolahan Produk Dendeng Daun Singkong Dan Nugget Udang Sebagai Potensi Usaha Masyarakat Kelurahan Teluk Makmur - Diah Anugrah Dipuja; Bagaspati L Sadewa; Anggi Nur AzkaRahma; Rahma Syahza; Reffi Devani; Syarifah Frisca Adelia Zafani; Difa Amalika Fadli; Mutia Agnes Amira Rosalin; Rayhan Dwi Nugraha Irawan; Lans Adi Jusuf Hutabarat (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2023)
The potential possessed by Teluk Makmur sub-district includes the agricultural and fisheries aspects, where in terms of agriculture it’s in the form of cassava plants and in terms of fisheries it’s in the form of shrimp. This is also related to the livelihoods of the community, the majority of whom are farmers, fishermen and entrepreneurs/MSMEs, so by utilizing the potential of the sub-district and the livelihoods of the community, the Kukerta team decided to hold a demonstration of organic cassava jerky and shrimp nuggets as an alternative for entrepreneurial sales products/ MSMEs. The aim of this demonstration is to motivate MSMEs to continue running and provide various variations of sales products originating from the potential of the sub-district. Community service activities were carried out at the Teluk Makmur Village Hall, Medang Kampai District, Dumai City on Saturday, July 29 2023 at 08.00 WIB until finished. Methods include direct explanations by Kukerta students from Teluk Makmur Village as well as field practice which is directly held in front of the participants present. This service activity took place successfully, which can be said to be due to the response given by all demonstration participants who were truly enthusiastic about everything.